CHOOSING TEACHING MATERIALS AND LEARNING MEDIA IN THE INDEPENDENT LEARNING CURRICULUM - Lira Hayu Afdetis Mana; Laspida Harti (STKIP PGRI Sumatera Barat, 2022)
This activity aims to provide direction to teachers so they can use various media according to the needs of students and those in the student environment. The teacher's freedom in choosing learning media in the independent curriculum can help students understand the material presented. This activity is a community service activity. This activity was carried out for one day with one meeting at one school. The implementation stages are, (1) introducing and reviewing material about Indonesian language teaching materials and learning media in the independent curriculum, (2) providing examples of teaching materials and learning media and providing training to teachers so they can apply teaching materials and media learning, and (3) teachers can use Indonesian language media and teaching materials in an independent curriculum that has been designed in such a way. The results of this activity show that the success of education depends on the quality of education in a country. The quality of education must be adjusted to the needs of students. To motivate students in the learning process, teacher expertise is needed in innovating teaching materials and learning media in the medical curriculum by paying attention to student characteristics and student learning types. Learning media is divided into three, namely auditory, visual, and kinesthetic.